The Virtuous Discourse of Adam Smith: A Liberal Regard for Prevailing Prejudice - Clark, Michael (George Mason University, 2011)
Recent academic work has attempted to change the interpretation of Adam Smith from the founder of free-market economics to ab proponent of something much more akin to the modern welfare state. This paper will attempt to refute those approaches by analyzing Adam Smith’s views on strategic politeness. The paper will show that Smith advocated an approach for political discussion that utilizes strategic yielding and caution when necessary. Smith related the approach to that of the Athenian official Solon who put forth laws that attempted to be ―the best that the people can bear.‖ The approach can lead one to moderation, non disclosure, or fudging of extreme views. According to Smith, there was virtue in considering and at times yielding to the prejudice of the public. The cautious nature of Smith’s approach has been misinterpreted in modern literature. Smith’s caution is being taken for mild to moderate interventionist support. While the works and ideas of Adam Smith remain foundational to modern economics the interpretation of Smith is changing. This paper defends the interpretation of Adam Smith as a strong proponent of liberty based on his strategic approach.
Working-paper. Paper analyzes Adam Smith's views on strategic politeness and how Adam Smith advocated for political discussion and that his work is still important today in modern economics.